Correlation between pulmonary embolism and blood cell count changes: Pulmonary embolism and blood cell count changes - Deng, Shuling; Lv, Mingyi; Long, Xiaofeng (Cellular and Molecular Biology, 2023)
Pulmonary embolism is one of the acute diseases of the respiratory system. This study investigates changes in red blood cell counts in pulmonary embolisms confirmed by scintigraphy. Counting red blood cells is essential in diseases, especially pulmonary embolism, because of the vital role of these cells. In this study, 25 patients with pulmonary embolism were selected. A group of 25 healthy volunteers was also considered as a control. At zero, 30, 60 minutes, 24, 48, and 72 hours, blood samples were taken from both control and patient groups, and red blood cells were counted according to the standard method. After extracting technetium-99m from the molybdenum generator, this substance was added to the MAA drug kit under particular conditions. After preparation, radiopharmaceutical 99mTC-MAA with 1.5 millicuries was injected intravenously into both groups. In this study, a significant increase in the red blood cell count of the patient group was observed on the first and second days of the disease. On the third day, this count returned to normal. These changes indicate the functioning of the body’s defense system and a response to reduce the complications caused by pulmonary embolism. Therefore, paying more attention to counting red blood cells in pulmonary embolism, along with other care, is recommended due to their particular function.